Direct and delayed effect of the plant Cleome amblyocarpa Barratte & Murb (Capparidaceae) on the two species of (Blattodea) Blattella germanica (Linnaeus, 1767) and Shelfordella lateralis (Walker, 1868) - Saliha BENHISSEN; Siham BOUNADJI; Feriel Kheira KEBAILI; Nora BELKHIRI; Wafa HABBACHI; Feriel ABBAS; Sonia Ancuţa SMAILI; Khellaf REBBAS (Studia Universitatis Babeș-Bolyai. Biologia, 2024)
Finding substantial substitution of chemical pesticides to control cockroaches, which were proved to link with multiple health issues, has become the major target of many researchers. In fact, subjecting this pest to the effects of toxic plants extracts is considered ideal to primarily avoid jeopardizing human health. This study is divided into two objectives. The first is to confirm the toxicity of the ethanolic extract from the plant Cleome amblyocarpa Barratte & Murb, on two species of urban cockroaches; which are Blattella germanica (Linnaeus, 1767) and Shelfordella lateralis (Walker, 1868), while the second is to verify the effect of the attractive odor of the extract on the feeding behavior of the two already mentioned species. Therefore, the findings demonstrated that the extract causes a mortality rate of 60% of B. germanica after 30 days of treatment at a high concentration of (3g/l). The mortality rate in S. lateralis does not exceed 6.7%. Further, findings exhibited that the proportion of B. germanica attracted by the smell of the plant soaked in hexane at a specified time (15, 30 and 60 minutes) was estimated at 40%, whereas that of S. lateralis exceeded 60%. The results provide the presence of toxic elements within the examined extract, suggesting the potential for developing bio-insecticides derived from Cleome amblyocarpa for utilization in the pesticide industry.